Implementation of the Triple Exponential Smoothing Method for Predicting Helmet Sales: Implementasi Metode Triple Exponential Smoothing untuk Prediksi Penjualan Helm - Saputro, Ronggo Bayu; Kartika, Kurnia Paranita; Puspitasari, Wahyu Dwi (Universitas Muhammadiyah Sidoarjo, 2022)
Helmet stock at the Trend Helmet store is very important to prepare, because it is for the readiness of goods to be sold in the future. Therefore, it is necessary to do forecasting to find out the estimated stock in the future. The method that can be used to predict the stock of goods for several periods at once is Triple Exponential Smoothing. Helmet stock forecasting results with Cargloss helmet sales data obtained a forecast for 2022. Alpha, beta and gamma used in this study were 0.3. Cargloss helmet sales forecast results in January as many as 379, February as many as 449, March as many as 431, April as many as 500, May as many as 483, June as many as 552, July as many as 534, August as many as 604, September as many as 586, October as many as 656, November as many as 638 , December as many as 707. The results of the calculation of accuracy with Mean Absolute Percentage Error with Alpha, Beta and Gamma values of 0.3 are 44.4%. Based on the value of Mean Absolute Percentage Error helmet sales forecasting with Triple Exponential Smoothing method is feasible to use.